Implementasi Pendekatan Arsitektur Perilaku pada Desain Lembaga Pemasyarakatan Klas IIA di Kabupaten Wajo - Ratriana; Alfiah; Viviana Basri (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Penitentiary is a place of rehabilitation for prisoners who have gone through the process of investigation, prosecution, examination of cases and court decisions. However, the condition that occurs in Indonesia is that the number of prisoners continues to increase and exceeds capacity so that there is a shortage of rehabilitation facilities and then the detention house is converted into a place of rehabilitation, so that it is not in accordance with the function of the building. Especially in Wajo district, there is the Sengkang Class IIB Detention Center which accommodates 335 Correctional Inmates (WBP) consisting of 262 inmates and 73 prisoners. So it is necessary to build a correctional facility in Wajo Regency. The design of this Correctional Institution uses the Behavioral Architecture theme. This behavioral architecture concept aims to present a prison that can accommodate and facilitate coaching programs so that the coaching function can be achieved through design by prioritizing aspects of privacy, circulation, personal space, territoriality, and security. Thus, it can support the success of the functi on of this design object to foster, educate and guide prisoners.